2020
DOI: 10.1186/s13287-020-01840-2
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent LPS exposure commands MSC immunoplasticity through TLR4 activation leading to opposite therapeutic outcome in EAE

Abstract: Background Mesenchymal stem cells (MSCs) have been recognized for their regenerative and anti-inflammatory capacity which makes them very attractive to cell therapy, especially those ones to treat inflammatory and autoimmune disease. Two different immune-phenotypes have been described for MSCs depending on which Toll-like receptor (TLR) is activated. MSC1 is endowed with a pro-inflammatory phenotype following TLR4 activation with LPS. On the other hand, anti-inflammatory MSC2 is induced by the activation of TL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 45 publications
1
48
0
Order By: Relevance
“…In this sense, in the proteomic analysis we found that the use of LPS+Stx in iPSC-MSC, in-duced the release of proteins related to the BP of "IL-12 mediated signalling pathway" such as PPIA, which is reported to promote apoptosis in endothelial cells and chemotaxis in inflammatory cells [36]. As Wong and Waterman et.al described in a previous work, we can speculate that activation of TLR4 in iPSC-MSC due to LPS resulted in the secretion of pro-inflammatory factors in the CM that are important for early injury responses, like migration and cell adhesion to ECM, but not to resolve tissue damage [9]. However, these mechanisms could prepare the microenvironment for later iPSC-MSC anti-inflammatory responses that could facilitate the restoration of tissue injury.…”
Section: Discussionmentioning
confidence: 64%
“…In this sense, in the proteomic analysis we found that the use of LPS+Stx in iPSC-MSC, in-duced the release of proteins related to the BP of "IL-12 mediated signalling pathway" such as PPIA, which is reported to promote apoptosis in endothelial cells and chemotaxis in inflammatory cells [36]. As Wong and Waterman et.al described in a previous work, we can speculate that activation of TLR4 in iPSC-MSC due to LPS resulted in the secretion of pro-inflammatory factors in the CM that are important for early injury responses, like migration and cell adhesion to ECM, but not to resolve tissue damage [9]. However, these mechanisms could prepare the microenvironment for later iPSC-MSC anti-inflammatory responses that could facilitate the restoration of tissue injury.…”
Section: Discussionmentioning
confidence: 64%
“…MSC1 is endowed with a proinflammatory phenotype following TLR4 activation with LPS. On the other hand, anti-inflammatory MSC2 is induced by the activation of TLR3 with Poly(I:C) [ 55 , 56 , 57 ]. MSC1 shows an increased synthesis and secretion of proinflammatory cytokines and chemokines, such as IL-6 and IL-8, whereas MSC2 has increased production of immunosuppressive mediators, such as IP-10 and CCL5.…”
Section: Discussionmentioning
confidence: 99%
“…MSC1 shows an increased synthesis and secretion of proinflammatory cytokines and chemokines, such as IL-6 and IL-8, whereas MSC2 has increased production of immunosuppressive mediators, such as IP-10 and CCL5. MSCs have high immunoplasticity, and the phenotype conversion can be caused by exogenous stimuli, such as proinflammatory cytokines or TLR agonists, as well as the duration of treatment [ 15 , 57 , 58 ]. The data on the effect of exogenous proinflammatory cytokines on MSCs are contradictory.…”
Section: Discussionmentioning
confidence: 99%
“…A few dozen cell-based therapies have obtained market authorization in several countries ( Cuende et al, 2018 ), and at least another dozen of approved MSC-based therapies are expected to reach the market by the year 2030 ( Olsen et al, 2018 ). We have recently demonstrated ( Kurte et al, 2020 ) that MSC’s high immunoplasticity depends on the exposure duration with the inflammatory milieu, leading into either an enhanced or an impairment therapeutic activity, a matter of great concern for their clinical use. Both the translational advances and the limitation of the use of MSC in some clinical applications have pushed the field toward exploring their therapeutic potential without the need for cell transplantation.…”
Section: Introductionmentioning
confidence: 99%